Effet de séchage des plantes médicinales de la famille des Lamiacées (Romarin) sur l’activité antibactérienne - Zbalah, Halima; Belarbi, Yamina (My University, 2018)
Herbal medicine is a traditional medicine used by the population, it is also the knowledge and use of therapeutic due usually plants properties to the active secondary metabolites “active principle”. In the work we dried one plant used in herbal medicine, « Rosmarinus officinalis» depends on different methods (drying in the Sun , in the jornal, in the plastique ). The results obtained determine the factors responsible for the perfect drying. Phytochemical tests reveal the effect of each type of drying on the content of the plants in active principales
Keywords: phytothérapie; plante médecinale; Rosmarinus officilanus; séchage; phytochimie; staphylococcus aureus; phytotherapy; plant medicinal; Rosmarinus officilanis; drying; phytochemistry; staphylococcus aureus.